Trends in functional programming : 20th International Symposium, TFP 2019, Vancouver, BC, Canada, June 12-14, 2019, Revised Selected Papers /: 20th International Symposium, TFP 2019, Vancouver, BC, Canada, June 12-14, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available